Incidence of resistant mastitis in dairy cows in Tamil Nadu, India (Journal of Applied and Natural Science, 2015)
The incidence of resistant mastitis in dairy cows in Tamil Nadu, India was 56.l %. The predominant resistant causative pathogen was Escherichia coli (50.64 %) followed by Staphylococcus aureus (44.25 %) and Methicillin resistant Staphylococcus aureus (5.11 %). Incidence of resistant mastitis was high in Holstein Friesian cross breed followed by Jersey cross breed and non descript. Highest incidence was observed in early stage of third lactation. In vitro antibiotic sensitivity test revealed the E. coli, S. aureus and MRSA organisms showed more sensitivity to enrofloxacin, amoxicillin+sulbactam, gentamicin and ceftriaxone and had highest resistant to penicillin followed by amoxicillin, oxytetracycline and methicillin. The study highlights the need for preventing the indiscriminate use of antibiotics.